2018
DOI: 10.3233/jad-161310
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic and Prognostic Value of a Dual-Tasking Paradigm in a Memory Clinic

Abstract: In our study, we found that patients with MCI and mild AD have increasing difficulties in dual-tasking compared to healthy elderly. Hence, the dual-tasking paradigm may be a potential complement in the diagnostic assessment in a typical clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 45 publications
4
43
1
Order By: Relevance
“…2). This finding confirms that performing the dual task is helpful in finding a difference between the CN and MCI group, which is in accordance with previous literature [11,32].…”
Section: Gait and Syndrome Diagnosissupporting
confidence: 93%
“…2). This finding confirms that performing the dual task is helpful in finding a difference between the CN and MCI group, which is in accordance with previous literature [11,32].…”
Section: Gait and Syndrome Diagnosissupporting
confidence: 93%
“…the relative time difference between single-and dual-task performances, did not discriminate between any of the groups in the current study. In previous studies, dual-task cost has been found to discriminate between mild AD and healthy controls [46] and between MCI and healthy controls [19,29], and has shown inconsistent results when discriminating between dementia disorders and MCI [18,19], and was not able to discriminate between MCI and SCI [18]. It may be argued that dual-task cost cannot differentiate between transitional diagnoses, because it captures subtle pathological changes and is therefore better considered an indicator of imminent cognitive decline [50].…”
Section: Discussionmentioning
confidence: 99%
“…Such methods could be useful either as frontline screening tools or as diagnostic tools aimed at facilitating early and potentially more effective interventions. Different kinds of dual-task tests have been suggested for these purposes [9,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…This kind of information is seldom presented in research [24]. The only dual-task study found in which the quality of participants' performances was analysed; performances analyses categorised performances as normal, moderate deviation, or severe deviation, which was apparently based on observations at the same time as the testing occurred [50]. In that study, it was found that 98% of healthy controls, 62% of those with MCI, and 35% of those with Alzheimer's disease were categorised as having normal performance, which emphasizes the importance of paying attention to and managing these phenomena to improve the test validity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, categorisation based on cautious analyses of TUGdt performances might be used as an outcome measure in its own right, since deviant performance can be associated with the progression from MCI to dementia [29]. It has been suggested that the qualitative evaluation of dual-tasking may outperform quantitative measures when it comes to differentiating between progressive and stable MCI [50], but this hypothesis still needs further investigation. It is preferable for such analyses to be based on video-recorded tests to ensure a high degree of reliability.…”
Section: Discussionmentioning
confidence: 99%